Method for producing positive electrode active material for lithium ion secondary battery

The method addresses the challenges of non-uniform coatings and high costs in manufacturing lithium-ion battery active materials by using a specific composition and processing steps to achieve a uniform titanium coating on nickel-containing hydroxides, resulting in improved capacity and cycle performance.

JP7669650B2Active Publication Date: 2025-04-30PROTERIAL LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2020147342
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-02
Publication Date
2025-04-30
Estimated Expiration
2040-09-02

AI Technical Summary

Technical Problem

Existing methods for manufacturing positive electrode active materials for lithium-ion secondary batteries face challenges such as non-uniform coating layers, high manufacturing costs, and reduced initial charge and discharge capacity due to uneven distribution of additive elements.

Method used

A method involving a composition formula Li1+aNi bCo cTi dM eO2+α, where M represents elements like Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and specific processing steps including suspension adjustment, pH control, coating treatment, drying, mixing, and calcination to achieve a uniform coating of titanium-containing elements on nickel-containing hydroxides.

Benefits of technology

This method enables a uniform and cost-effective coating of titanium-containing elements on nickel-containing hydroxides, resulting in a positive electrode active material with high nickel content, improved charge/discharge capacity, and enhanced cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669650000003
    Figure 0007669650000003
  • Figure 0007669650000004
    Figure 0007669650000004
  • Figure 0007669650000005
    Figure 0007669650000005
Patent Text Reader

Abstract

To uniformly coat, on a particle surface of a hydroxide or composite hydroxide, an element including titanium, in a positive electrode active material with high Ni ratio, the positive electrode active material having a nickel content of 80% or more.SOLUTION: A method for producing a positive electrode active material for a lithium ion secondary battery includes: a coating step of adding at least one of a mixed aqueous solution obtained by adding a hydrogen peroxide solution to a titanium solution or a metal mixed aqueous solution obtained by adding a hydrogen peroxide solution to a titanium solution, the metal mixed aqueous solution including at least one element of M, to a suspension of a nickel-containing hydroxide or a suspension of a nickel-containing composite hydroxide including the M, the suspension being adjusted in nickel concentration, agitating the suspension, and coating the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide including the M with a titanium compound or a compound including a titanium compound and at least one element of the M; a drying step of removing moisture from a hydroxide subjected to the coating step to obtain dry powder; a mixing step of mixing the dry powder and a lithium compound; and a firing step of firing the obtained mixed powder.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive electrode active material for a lithium ion secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries are widely used as lightweight secondary batteries with high energy density. Regarding the positive electrode active material, which greatly affects the battery characteristics, in addition to establishing high capacity and mass production, studies are being conducted on reducing the resistance of lithium ions and stabilizing the crystal structure. Lithium transition metal composite oxides with an α-NaFeO2 type crystal structure (hereinafter sometimes referred to as a layered structure) are widely known as positive electrode active materials for lithium-ion secondary batteries. Traditionally, LiCoO2 has been used as an oxide with a layered structure, but due to demands for high capacity and mass production, ternary systems represented by Li(Ni,Co,Mn)O2 and nickel systems in which LiNiO2 is substituted with different elements have been developed. Among lithium transition metal composite oxides with a layered structure, nickel-based oxides have the disadvantage of not necessarily having good life characteristics. However, nickel-based oxides are composed of nickel, which is cheaper than cobalt and other metals, and have relatively high capacity, so they are expected to be used in a variety of applications. In particular, there are high expectations for chemical compositions with a high ratio of nickel per metal other than lithium (Ni, Co, Mn, etc.).

[0003] For example, Patent Document 1 describes a method in which nickel-cobalt-manganese composite hydroxide particles are slurried in an aqueous solution containing an additive element M, and while controlling the pH to a predetermined level, an aqueous solution containing one or more types of additive elements M is added to cause the additive elements M to precipitate on the surfaces of the nickel-cobalt-manganese composite hydroxide particles by a crystallization reaction, thereby uniformly coating the surfaces with the additive elements M. Patent Document 1 also describes a lithium transition metal compound powder for use as a positive electrode material for lithium secondary batteries, which is produced by spray-drying a slurry in which nickel-cobalt-manganese composite hydroxide particles and a salt containing one or more types of additive elements M are suspended.

[0004] Further, Patent Document 2 describes that nickel cobalt composite hydroxide is slurried with water at room temperature, and then, without adjusting the pH of the slurry, an aqueous titanium sulfate solution adjusted to pH 1 with an aqueous sodium hydroxide solution and an aqueous sodium hydroxide solution with a concentration of 12% by weight are simultaneously added and stirred so that the mixing ratios of nickel, cobalt and titanium are 84:15:1 in molar ratio, and a positive electrode material for a lithium ion secondary battery obtained by adjusting the pH to 8 to 10.5 is described.

[0005] Further, Patent Document 3 has a lithium compound layer on at least a part of its surface and a central part other than that, and the composition is Li t1 Ni 1-x-y Co x M 1 y M 2 z O2 (where M 1 and M 2 are at least one element selected from the group consisting of Mg, Al, Ca, Ti, V, Cr, Mn, Zr, Nb, Mo and W, and are represented by 0.97 < t1 ≦ 1.10, 0 ≦ x ≦ 0.22, 0 ≦ y ≦ 0.15, 0 < z ≦ 0.05), and a positive electrode material for a lithium ion secondary battery is described.

Prior Art Documents

Patent Documents

[0006]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of the Invention

Problems to be Solved by the Invention

[0007] In Patent Documents 1 and 2, the coating additive element is likely to aggregate on the surface of the composite hydroxide, forming a non-uniform coating layer. In addition, the additive element may not be coated on the surface of the composite hydroxide, but may exist alone. The obtained positive electrode active material may have a localized thickness of more than a certain level, which may reduce Li desorption / insertion during charging and cause a deterioration in the initial charge / discharge capacity. Patent Document 3 uses metal alkoxide and also uses an organic substance to prevent hydrolysis, which makes it difficult to handle and requires expensive raw materials, resulting in high production costs.

[0008] Therefore, the present invention provides a method for producing a positive electrode active material with a high Ni ratio, in which the nickel content is set to 80% or more, and aims to provide a method for producing a positive electrode active material for lithium ion secondary batteries (hereinafter sometimes simply referred to as "positive electrode active material") through a suitable configuration for obtaining a precursor in which an element containing at least titanium is coated cheaply, safely, and uniformly on the particle surface of a nickel-containing hydroxide or a nickel-containing composite hydroxide containing M. [Means for solving the problem]

[0009] The present invention relates to a compound having the formula (1); Li 1+a Ni b Co c Ti d M e O 2+α (1) [In the composition formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and -0.1 <a<0.1、0.8≦b<1.0、 0.01 ≦c<0.2, 0.01≦d<0.05, 0≦e<0.2, -0.1<α<0.1, b+c+d+e=1 are satisfied. 。 The present invention relates to a method for producing a positive electrode active material for a lithium ion secondary battery, the positive electrode active material comprising a lithium transition metal composite oxide represented by the formula (1), Add the cobalt-containing metal solution and the alkaline solution at the same time, adjust the pH to 6-10, and stir. Titanium solution mixed with hydrogen peroxide andAdd an alkaline aqueous solution at the same time to adjust the pH to 6-10, and stir to separate the titanium compound and the cobalt compound. And The method for producing a positive electrode active material for a lithium ion secondary battery includes the steps of: a coating step of coating a surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M; a drying step of removing moisture from the hydroxide that has been subjected to the coating step to obtain a dry powder; a mixing step of mixing the dry powder with a lithium compound; and a calcination step of calcining the obtained mixed powder.

[0010] The present invention also relates to a compound having the formula (1); Li 1+a Ni b Co c Ti d M e O 2+α (1) [In the composition formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and -0.1 <a<0.1、0.8≦b<1.0、 0.01 ≦c<0.2, 0.01≦d<0.05, 0≦e<0.2, -0.1 <α<0.1, b+c+d+e=1 are satisfied. 。 The present invention relates to a method for producing a positive electrode active material for a lithium ion secondary battery, the positive electrode active material comprising a lithium transition metal composite oxide represented by the formula (1), Add the cobalt-containing metal solution and the alkaline solution at the same time, adjust the pH to 6-10, and stir. Titanium solution mixed with hydrogen peroxide and Add an alkaline aqueous solution at the same time to adjust the pH to 6-10, and stir to separate the titanium compound and the cobalt compound. And The method for producing a positive electrode active material for a lithium ion secondary battery includes a coating process for coating a surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M, a first firing process for firing the hydroxide that has been subjected to the coating process to obtain a composite oxide powder, a mixing process for mixing the composite oxide powder with a lithium compound, and a second firing process for firing the obtained mixed powder.

[0011] In the present invention, the following embodiment is preferable. That is, in the coating treatment step, It is preferable to simultaneously add a mixed metal aqueous solution containing at least one element of M and an alkaline aqueous solution to adjust the pH to 6 to 10, and coat the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M. In the coating treatment step, the amount of hydrogen peroxide added is preferably 0.1 to 4.0 mol per mol of titanium in the mixed aqueous solution or the mixed metal aqueous solution. In the coating treatment step, it is preferable that the mixed aqueous solution or the mixed metal aqueous solution has a molar concentration of 0.01 to 3.0 mol / L. The coating process can be repeated several times. Furthermore, it is preferable to carry out the coating treatment so that the ratio of the tap density (TD2) of the nickel-containing hydroxide powder or the nickel-containing composite hydroxide powder containing M after the coating treatment to the tap density (TD1) of the nickel-containing hydroxide powder or the nickel-containing composite hydroxide powder containing M, TD2 / TD1, is 0.9 or more. Effect of the Invention

[0012] According to the present invention, in a positive electrode active material with a high Ni ratio in which the nickel content is 80% or more, the particle surfaces of a nickel-containing hydroxide or a nickel-containing composite hydroxide containing M can be coated with an element containing at least titanium at low cost, safely, and uniformly. [Brief description of the drawings]

[0013] [Figure 1A] FIG. 2 is a flow chart showing an example of a method for producing a positive electrode active material according to the present invention. [Figure 1B] FIG. 4 is a flow chart showing another example of the method for producing a positive electrode active material of the present invention. [Figure 1C] FIG. 4 is a flow chart showing another example of the method for producing a positive electrode active material of the present invention. [Figure 1D] FIG. 4 is a flow chart showing another example of the method for producing a positive electrode active material of the present invention. [Diagram 2] FIG. 1 is a partial cross-sectional view illustrating an example of a lithium ion secondary battery. [Diagram 3] 1 is an SEM image (magnification: 5000) of Example 1 of the present invention. [Figure 4] 1 is an SEM image (magnification: 5000 times) of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, a method for producing a positive electrode active material for a lithium ion secondary battery according to one embodiment of the present invention will be described. First, the positive electrode active material and chemical composition will be described, and then the production method and the lithium ion secondary battery will be described. In the following, a numerical range expressed using "~" includes the numerical values ​​written before and after "~" as the lower limit and upper limit.

[0015] <Cathode active material> The positive electrode active material according to the present embodiment includes a lithium transition metal composite oxide having a layered α-NaFeO2 type crystal structure and containing lithium and a transition metal. This positive electrode active material is mainly composed of primary particles of the lithium transition metal composite oxide and secondary particles formed by agglomeration of a plurality of primary particles. The lithium transition metal composite oxide has a layered structure as a main phase that allows insertion and desorption of lithium ions.

[0016] The positive electrode active material according to this embodiment may contain, in addition to the lithium transition metal composite oxide which is the main component, unavoidable impurities derived from the raw materials or the manufacturing process, other components which coat the lithium transition metal composite oxide particles, such as a boron component, a phosphorus component, a sulfur component, a fluorine component, an organic substance, and other components which are mixed together with the lithium transition metal composite oxide particles.

[0017] The positive electrode active material for a lithium ion secondary battery according to the present invention has the following composition formula (1): Li 1+a Ni b Co c Ti d M e O 2+α (1) [However, in the compositional formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and -0.1 < a < 0.1, 0.8 ≤ b < 1.0, 0 ≤ c < 0.2, 0.01 ≤ d < 0.05, 0 ≤ e < 0.2, -0.2 < α < 0.2, and b + c + d + e = 1. It is a positive electrode active material for a lithium-ion secondary battery containing a lithium transition metal composite oxide represented by the formula.]

[0018] In the lithium transition metal composite oxide represented by the compositional formula (1), the proportion of nickel per metal excluding lithium is 80% or more. That is, in terms of the atomic fraction with respect to the total of Ni, Co, Ti, and M, Ni is contained at 80 at% or more. Since the nickel content is high, it is a nickel-based oxide capable of realizing a high discharge capacity. Also, since the nickel content is high, the raw material cost is lower compared to LiCoO2, etc., and it is excellent from the viewpoint of productivity including the raw material cost.

[0019] Generally, a lithium transition metal composite oxide with a high nickel content has the property that its crystal structure tends to become unstable during charge and discharge. In the crystal structure, Ni forms a layer composed of MeO2 (Me represents a metal element such as Ni). There are many tetravalent Ni. Since tetravalent Ni easily becomes stable divalent Ni, it transfers to a NiO-like crystal structure from near the surface of the crystal structure, resulting in a decrease in capacity and an increase in resistance.

[0020] Therefore, as described above, for the surface structure stabilization, a stable additive element that does not contribute to charge and discharge is arranged on the crystal surface. Although the above-mentioned Patent Documents 1 to 3 are examples thereof, aluminum or titanium has been coated to substitute for nickel to achieve structure stabilization.

[0021] However, the coating of the additive element is likely to aggregate on the surface of the composite hydroxide, forming a non-uniform coating layer. Also, the additive element may not be coated on the surface of the composite hydroxide and may exist independently. The oxide obtained from these processes has a certain thickness or more locally, which may reduce the Li desorption / insertion during charging and cause a deterioration of the initial charge / discharge capacity.

[0022] In this embodiment, a manufacturing method capable of forming a uniform coating layer has been found, and as a result, a high charge / discharge capacity can be obtained.

[0023] (chemical composition) Here, the significance of the chemical composition represented by the composition formula (1) will be explained.

[0024] In the composition formula (1), a is preferably more than -0.1 and less than 0.1, more preferably -0.04 or more and 0.04 or less, and even more preferably -0.02 or more and 0.02 or less. a represents the excess or deficiency of lithium with respect to the stoichiometric ratio Li(Ni,Co,Ti,M)O2. a is not the charge value at the time of raw material synthesis, but the value in the lithium transition metal composite oxide obtained by firing. When the excess or deficiency of lithium in the composition formula (1) is excessive, that is, when the composition has too little lithium or too much lithium relative to the total of Ni, Co, Ti, and M, the synthesis reaction does not proceed properly during firing, and cation mixing in which nickel is mixed into the lithium site is likely to occur, or crystallinity is likely to decrease. In particular, when the proportion of nickel is increased to 80% or more, the occurrence of such cation mixing and the decrease in crystallinity are likely to become significant, and the discharge capacity and charge / discharge cycle characteristics are likely to be impaired. In contrast, when a is in the above-mentioned range, cation mixing is easily reduced, and various battery performances can be improved. Therefore, even in a composition with a high nickel content, a high discharge capacity, good rate characteristics, and charge / discharge cycle characteristics can be obtained.

[0025] The nickel coefficient b in the composition formula (1) is 0.8 or more and less than 1.0. When b is 0.80 or more, a higher discharge capacity can be obtained compared to other nickel-based oxides with a low nickel content and ternary oxides represented by Li(Ni,Co,M)O2. In addition, the amount of transition metals that are rarer than nickel can be reduced, which reduces raw material costs.

[0026] The nickel coefficient b may be 0.85 or more, 0.90 or more, or 0.92 or more. The larger b is, the higher the discharge capacity tends to be. The nickel coefficient b may be 0.95 or less, 0.90 or less, or 0.85 or less. The smaller b is, the smaller the lattice distortion or crystal structure change associated with the insertion or desorption of lithium ions becomes, and the less likely cation mixing in which nickel is mixed into the lithium site or the less likely the crystallinity is reduced during firing, so that good rate characteristics and charge / discharge cycle characteristics tend to be obtained.

[0027] The coefficient c of cobalt in the composition formula (1) is 0 or more and less than 0.2. Cobalt may be added intentionally, or may have a composition ratio equivalent to unavoidable impurities. When the cobalt is in the above range, the crystal structure becomes more stable, and effects such as suppression of cation mixing in which nickel is mixed into the lithium site can be obtained. Therefore, high discharge capacity and good charge-discharge cycle characteristics can be obtained. On the other hand, if the cobalt is excessive, the raw material cost of the positive electrode active material increases. In addition, the ratio of other transition metals such as nickel decreases, and there is a risk that the discharge capacity will be low or the effect of the metal element represented by M will be reduced. On the other hand, if c is in the above numerical range, the raw material cost of the lithium transition metal composite oxide that shows high discharge capacity, good rate characteristics and charge-discharge cycle characteristics can be reduced.

[0028] The cobalt coefficient c may be 0.01 or more, 0.02 or more, 0.03 or more, or 0.04 or more. The larger c is, the more effectively the effect of the elemental substitution of cobalt is obtained, and therefore, there is a tendency for better charge / discharge cycle characteristics to be obtained. The cobalt coefficient c may be 0.06 or less, 0.03 or less, or 0.01 or less. The smaller c is, the more the raw material cost can be reduced.

[0029] The coefficient d of titanium is 0.01 or more and less than 0.05. If d is less than 0.01, there is no effect of stabilizing the structure, and if d is 0.05 or more, the charging capacity is reduced. Since Ti can be tetravalent, it has a strong bond with O and is highly effective in stabilizing the crystal structure. In addition, the molecular weight is relatively small, so the reduction in the theoretical capacity of the positive electrode active material when it is added is small.

[0030] The coefficient d of titanium may be 0.015 or more, 0.02 or more, or 0.03 or more. The larger d is, the more effective the effect of structural stability can be obtained. The coefficient d of titanium may be 0.04 or less, 0.35 or less, or 0.15 or less. The smaller d is, the higher the discharge capacity tends to be.

[0031] The coefficient e of M in the composition formula (1) is 0 or more and less than 0.2. If the metal element represented by M is excessive, the ratio of other transition metals such as nickel will be low, and the discharge capacity of the positive electrode active material may be low. On the other hand, if e is within the above-mentioned numerical range, a higher discharge capacity, good rate characteristics and charge / discharge cycle characteristics tend to be obtained.

[0032] The coefficient e of M may be 0.01 or more, 0.03 or more, 0.05 or more, or 0.10 or more. The larger e is, the more effectively the effect of element substitution of the metal element represented by M is obtained. The coefficient e of M may be 0.15 or less, 0.10 or less, or 0.05 or less. The smaller e is, the higher the proportion of other transition metals such as nickel, and the discharge capacity tends to be higher.

[0033] In the composition formula (1), α is greater than -0.1 and less than 0.1. α represents the excess or deficiency of oxygen relative to the stoichiometric ratio of Li(Ni,Co,Ti,M)O2. If α is within the above-mentioned numerical range, the crystal structure has few defects, and the appropriate crystal structure can provide high discharge capacity and good charge / discharge cycle characteristics. The value of α can be measured by inert gas fusion-infrared absorption method.

[0034] (Secondary particles) The average particle size of the primary particles of the positive electrode active material is preferably 0.05 μm or more and 2 μm or less. By making the average particle size of the primary particles of the positive electrode active material 2 μm or less, a reaction field of the positive electrode active material can be secured, and a high discharge capacity can be obtained. It is more preferably 1.5 μm or less, and even more preferably 1.0 μm or less. In addition, the average particle size of the secondary particles of the positive electrode active material is preferably, for example, 3 μm or more and 50 μm or less.

[0035] (specific surface area) The lithium transition metal composite oxide represented by the composition formula (1) preferably has a BET specific surface area of ​​0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more. The BET specific surface area is preferably 1.5 m 2 / g or less, more preferably 1.2m 2 / g or less. BET specific surface area is 0.1m 2 When the BET specific surface area is 1.5 m / g or more, a positive electrode having a sufficiently high molding density and a sufficiently high packing rate of the positive electrode active material can be obtained. 2 When the lithium transition metal composite oxide has a molecular weight of 0.1 to 1.0 g / g or less, the lithium transition metal composite oxide is less likely to break, deform, or fall off when it is pressed into shape or when the volume of the oxide changes during charging and discharging, and the pores are prevented from sucking up the binder. This improves the coatability and adhesion of the positive electrode active material, resulting in a high discharge capacity, good rate characteristics, and good charge and discharge cycle characteristics.

[0036] (composition analysis) The average composition of the particles of the positive electrode active material can be confirmed by high-frequency inductively coupled plasma (ICP), atomic absorption spectrometry (AAS), or the like.

[0037] (Positive electrode active material powder packing density (tap density)) The powder packing density (tap density) of the positive electrode active material was determined by placing 10 g of powder in a 20 ml glass measuring cylinder, tapping 200 times with an immersion specific gravity meter, and measuring the powder volume.

[0038] <Method of manufacturing positive electrode active material> The positive electrode active material according to the present embodiment can be produced by ensuring the synthesis reaction between lithium and nickel, cobalt, titanium, etc. under appropriate firing conditions under a raw material ratio such that the lithium transition metal composite oxide has a chemical composition represented by composition formula (1). The method for producing the positive electrode active material according to the present embodiment will be described below with reference to the drawings.

[0039] The method for producing a positive electrode active material for a lithium ion secondary battery according to this embodiment is roughly divided into two production steps, production method 1 and production method 2. 1A, for example, a suspension of nickel-containing hydroxide or a suspension of nickel-containing composite hydroxide containing the M, in which the nickel concentration is adjusted to 20 mass% or more and 80 mass% or less, is prepared, and either a mixed aqueous solution in which hydrogen peroxide (H2O2) is added to a titanium solution, or a mixed aqueous metal solution in which hydrogen peroxide is added to a titanium solution and which contains at least one element selected from the M, is added thereto. At this time, it is preferable to simultaneously add an alkaline aqueous solution together with the mixed aqueous solution or the mixed aqueous metal solution to adjust the pH of the suspension. Thereafter, the method includes a coating process in which the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M is coated with a titanium compound or a compound containing a titanium compound and at least one element selected from the M elements by, for example, stirring the mixed suspension at 20°C or higher and 80°C or lower; a drying process in which the coated hydroxide powder is heated to 60°C or higher and 150°C or lower to remove moisture to obtain a dry powder; a mixing process in which the obtained dry powder is mixed with a lithium compound; and a firing process (second firing process) in which the obtained mixed powder is fired at 650°C or higher and 850°C or lower in an oxygen atmosphere.

[0040] In the manufacturing method 1, as shown in Fig. 1C, the coating process can be performed by separately adding a mixed aqueous solution obtained by adding hydrogen peroxide water to a titanium solution and a metal solution containing at least one element selected from the group consisting of M. Titanium can be coated with the mixed aqueous solution, and the M element can be coated with the metal solution containing M. Alternatively, cobalt can be coated by separately adding a metal solution containing cobalt.

[0041] 1B, for example, a suspension of a nickel-containing hydroxide or a suspension of a nickel-containing composite hydroxide containing the M, in which the nickel concentration is adjusted to 20 mass % or more and 80 mass % or less, is prepared, and either a mixed aqueous solution in which hydrogen peroxide is added to a titanium solution, or a mixed aqueous metal solution in which hydrogen peroxide is added to a titanium solution and which contains at least one element selected from the M, is added thereto. At this time, it is preferable to simultaneously add an alkaline aqueous solution together with the mixed aqueous solution or the mixed aqueous metal solution to adjust the pH of the suspension. Thereafter, the method includes a coating process in which the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M is coated with a titanium compound or a compound containing a titanium compound and at least one element selected from the M elements by, for example, stirring the mixed suspension at 20°C or higher and 80°C or lower; a first firing process in which the coated hydroxide powder is fired at 300°C or higher and 700°C or lower in an oxygen atmosphere to obtain a composite oxide powder; a mixing process in which the obtained composite oxide powder is mixed with a lithium compound; and a second firing process in which the obtained mixed powder is fired at 650°C or higher and 850°C or lower in an oxygen atmosphere.

[0042] In the manufacturing method 2, as shown in Fig. 1D, the coating process can be performed by separately adding a mixed aqueous solution obtained by adding hydrogen peroxide water to a titanium solution and a metal solution containing at least one element selected from the group consisting of M. Titanium can be coated with the mixed aqueous solution, and the M element can be coated with the metal solution containing M. Alternatively, cobalt can be coated by separately adding a metal solution containing cobalt.

[0043] As described above, manufacturing method 1 has a coating step, a drying step, a mixing step, and a firing step (same as the second firing step described below), while manufacturing method 2 has a coating step, a first firing step, a mixing step, and a second firing step. Manufacturing methods 1 and 2 differ in the drying step and the first firing step, but are characterized by the common coating step. That is, they are characterized by using a mixed aqueous solution in which hydrogen peroxide water is added to a titanium solution, or a mixed aqueous metal solution in which at least one M element is added to this.

[0044] It is to be noted that steps other than these steps may be added. For example, if a large amount of lithium hydroxide or lithium carbonate remains in the positive electrode active material obtained in the baking step, the electrode mixture in the form of a slurry will gel in the mixture coating step for producing a positive electrode, so that the remaining lithium hydroxide or lithium carbonate can be reduced by adding a water washing step and a drying step after water washing following the second baking step. In addition, when the water washing and drying steps after water washing are added, the positive electrode active material obtained after the water washing and drying steps after water washing is to satisfy the composition formula (1). In the case where the process ends with the second baking step, the positive electrode active material obtained after the baking step is to satisfy the composition formula (1). This is because the value of a in the positive electrode active material in the state in which it is used in a battery is important. Each manufacturing step will be explained below.

[0045] (Coating process) First, a suspension is prepared by adding pure water to a nickel-containing hydroxide. Alternatively, a suspension solution is prepared by adding pure water to a nickel-containing composite hydroxide containing M. The nickel concentration of the suspension solution is preferably 20 to 80 mass%, more preferably 30 to 70 mass%, and even more preferably 40 to 60 mass%. If it is less than 20 mass%, the contact opportunity between the hydroxide and the additive element is reduced, and the additive element may not be uniformly coated on the hydroxide surface. If it exceeds 80 mass%, it becomes difficult to stir the suspension, and it may be difficult to uniformly coat the hydroxide surface. In addition, the equipment for stirring is expensive. On the other hand, a mixed aqueous solution is prepared by adding hydrogen peroxide (H2O2) to a titanium solution. Alternatively, a mixed aqueous metal solution may be prepared by adding at least one element of the M elements to the mixed aqueous solution.

[0046] Next, the mixed aqueous solution containing hydrogen peroxide and an alkaline aqueous solution are added to the suspension at the same time. The pH of the mixed solution is adjusted to 6 to 10 by the alkaline aqueous solution added at this time. If the pH is less than 6, the nickel-containing hydroxide to be coated or the nickel-containing composite hydroxide containing M may be partially dissolved, which may result in a deviation in the composition of the resulting lithium transition metal composite oxide. If the pH is more than 10, the coating element may re-dissolve, which may result in a deviation in the composition. The pH can be adjusted to a predetermined pH by adding the metal solution at a constant rate while adjusting the addition rate with the alkaline aqueous solution. Alternatively, the above method may be carried out by using a mixed metal aqueous solution containing the element M, and adding the mixed metal aqueous solution and an alkaline aqueous solution to the suspension at the same time. In this case, the pH of the mixed suspension is also adjusted to 6 to 10.

[0047] The alkaline aqueous solution is not particularly limited, and may be one in which an alkali metal hydroxide such as sodium hydroxide is dissolved. The concentration of this alkaline aqueous solution is not particularly limited, and may be any concentration that can maintain a predetermined pH during the coating treatment.

[0048] The form of titanium or M element to be coated is not particularly limited, but it is preferable to coat it as a water-soluble compound. For example, in the case of titanium, a titanium sulfate solution, titanyl sulfate, etc. can be used. Titanium sulfate solution is easy to obtain and is preferable in that it is a solution and therefore does not require the work of dissolving crystals to make a solution. In addition, in the case of M element, sulfate, nitrate, chloride, etc. can be used. On the other hand, the nickel-containing hydroxide to be coated or the nickel-containing composite hydroxide containing M may be a hydroxide containing a metal element such as cobalt, manganese or aluminum in addition to nickel, and may contain a coating element.

[0049] In this embodiment, titanium or at least two kinds of metal elements including titanium are coated on the surface of nickel-containing hydroxide or nickel-containing composite hydroxide including M, and the method is characterized in that metal hydrogen peroxide (H2O2) is added to the mixed aqueous solution (titanium) or the mixed aqueous solution of metals (titanium and M element). It was found that adding hydrogen peroxide to these aqueous solutions in advance is effective for uniform coating. That is, by adding hydrogen peroxide to the titanium solution, a yellow or brown peroxo titanium complex is formed, and the hydrolysis reaction can be suppressed. In general, titanium solutions are very susceptible to hydrolysis, and even at a pH of about 2, hydroxide precipitates are generated. The generated hydroxide has a very strong cohesive force, making uniform coating difficult. However, when hydrogen peroxide is added to the titanium solution, the pH at which the precipitate precipitates due to the formation of the complex increases, and the cohesive force of the generated hydroxide weakens. This action makes it possible to achieve uniform coating. There is also a method of suppressing hydrolysis using metal alkoxide and organic matter, but it is expensive and difficult to handle. Compared to expensive metal alkoxides, hydrogen peroxide is inexpensive and helps reduce costs.

[0050] The amount of hydrogen peroxide (H2O2) added is preferably 0.1 to 4.0 moles per mole of titanium in the mixed aqueous solution or the mixed metal aqueous solution. More preferably, it is 0.5 to 3.0 moles, and even more preferably, it is 0.5 to 2.0 moles. If it is 0.1 mole or more, the complex is sufficiently formed, and if it is 4.0 moles or less, the complex is effectively formed. In other words, if it exceeds 4.0 moles, the hydrogen peroxide becomes excessive, which is not preferable because it increases the raw material cost. If it is within the above range, the added hydrogen peroxide effectively acts with titanium, so that a sufficient complex can be formed and the raw material cost does not increase.

[0051] The molar concentration of the mixed aqueous solution or the mixed metal aqueous solution to be coated is preferably 0.01 to 3.0 mol / L. More preferably, it is 0.05 to 2.0 mol / L, and even more preferably, it is 0.1 to 1.0 mol / L. At 0.01 mol / L or more, the productivity increases, and at 3.0 mol / L or less, the generated compound (hydroxide) can be uniformly coated on the surface. Therefore, within the above range, the productivity does not decrease significantly, and the generated compound (hydroxide) can be uniformly coated on the surface.

[0052] The temperature during the coating treatment is preferably 20 to 80°C, more preferably 20 to 70°C, and even more preferably 30 to 50°C. By setting the temperature at 20°C or higher, the generated compound (hydroxide) can be easily uniformly coated on the surface. Also, if the temperature is 80°C or lower, the amount of water evaporation can be suppressed to keep the concentration of the suspension constant, uniform stirring can be performed, and the surface can be uniformly coated. Therefore, within the above range, uniform stirring can be performed, and the generated compound (hydroxide) can be uniformly coated on the surface.

[0053] In the coating process, when two or more elements are to be coated, metal solutions containing the respective elements, for example, a metal solution containing Co and an M metal solution containing element M, are prepared and added individually and simultaneously with the alkaline aqueous solution to perform the coating process (see Figs. 1C and 1D). In this case, the elements may be added one by one in order to perform the coating process, or may be added as a mixed solution to perform the coating process. These coating processes may be performed multiple times, and in this case, the pH of the mixed suspension is adjusted to 6 to 10.

[0054] In addition, in the coating process of this embodiment, an index for determining whether the coating is uniform or not was found by taking the ratio of the tap densities of the powder before and after the coating process. That is, the tap density (g / cm) of the composite hydroxide powder obtained by the coating process to the tap density (TD1) of the nickel-containing hydroxide powder or the nickel-containing composite hydroxide powder containing M before the coating process was calculated. 3) (TD2) is 0.9 or more in terms of TD2 / TD1 ratio, it can be considered that the coating is uniform. This will be explained in the examples below. The tap density was measured in the same manner as the measurement of the powder packing density (tap density) of the positive electrode active material described above.

[0055] (drying process) The mixed suspension obtained by the coating treatment is subjected to solid-liquid separation. For solid-liquid separation, a press filter, a centrifuge, or the like can be used, and the mixed suspension is filtered and washed. The hydroxide powder obtained after the coating treatment is preferably heated to 60°C to 150°C using a dryer or the like to remove moisture, and is made into a dry powder represented by the following composition formula (2). In this way, a coated dry powder can be obtained. Ni x Co y Ti z M e (OH) 2+α (2) [In the composition formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and is a number satisfying 0.8≦x<1 and x+y+z+t=1.]

[0056] (First firing process) As described above, a calcination step may be performed instead of the drying step. That is, the hydroxide powder coated as described above may be subjected to a first calcination step to obtain a composite oxide powder. In the first calcination step, the composite oxide powder represented by the following composition formula (3) is preferably obtained by calcining at a temperature of 300°C or higher to 700°C or lower in an oxygen atmosphere. A temperature of 300°C or higher is preferable for sufficient decomposition of the hydroxide, and if the temperature exceeds 700°C, segregation of the coated element proceeds, and the discharge capacity tends to decrease. The calcination time is 0.5 to 10 hours. This makes it possible to obtain a coated oxide powder. Ni x Co y Ti z M e O 2+α (3) [In the composition formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and is a number satisfying 0.8≦x<1 and x+y+z+t=1.]

[0057] (Mixing process) In the mixing step of mixing the lithium compound, either the above-mentioned dry powder or the above-mentioned composite oxide powder can be used, but in order to stably obtain a lithium transition metal composite oxide, it is preferable to use the oxide powder obtained by carrying out the first firing step. When the dry powder is used, it is easy and inexpensive to produce, but the moisture content may vary depending on the drying state, which may lead to unstable production.

[0058] In the mixing step, in which a lithium compound and, for example, a composite oxide powder are weighed out and mixed in predetermined amounts, the lithium is adjusted to be contained in a molar ratio of more than 0.90 and less than 1.10 relative to the total amount of metal elements in the composite oxide powder. If the molar ratio is 0.90 or less, the crystallinity of the resulting powder is poor. In addition, the capacity during the charge / discharge cycle is significantly reduced due to a shortage of lithium involved in charge / discharge. On the other hand, if the molar ratio is 1.10 or more, lithium is present at the site where nickel should be in order to form a layered structure, and the crystallinity of the resulting lithium transition metal composite oxide is poor.

[0059] Examples of the lithium-containing compound include lithium carbonate, lithium acetate, lithium nitrate, lithium hydroxide, lithium chloride, lithium sulfate, etc. In addition, it is preferable to use lithium carbonate or lithium hydroxide, since the gas generated in the firing step is water vapor or carbon dioxide gas, it causes less damage to the production equipment, is inexpensive, and has excellent industrial applicability and practicality.

[0060] In the above, it is desirable to mix the coated powder and the lithium compound sufficiently to prevent fine powder from being generated. If the mixing is insufficient, the ratio of Li and M may vary, and sufficient battery characteristics may not be obtained. A general mixer may be used for mixing. For example, a shaker mixer, V blender, etc. may be used.

[0061] (Second baking process (baking process)) The mixed powder obtained in the mixing step is subjected to a second firing step (same as the firing step in the manufacturing method 1) in which the mixed powder obtained in the mixing step is fired, for example, in an oxygen atmosphere at 650°C or higher and 850°C or lower. In the second firing step, if the heat treatment temperature is 650°C or higher, nickel can be sufficiently oxidized to suppress cation mixing, while the crystal grains of the lithium transition metal composite oxide can be grown to an appropriate grain size and specific surface area. In addition, titanium and the metal element represented by M can be sufficiently oxidized to increase the proportion of divalent nickel. Since a main phase is formed in which the lattice constant of the a-axis is large and the lattice distortion or crystal structure change associated with the insertion and desorption of lithium ions is reduced, a high discharge capacity, good charge / discharge cycle characteristics, and output characteristics can be obtained. In addition, if the heat treatment temperature is 850°C or lower, lithium is unlikely to volatilize and the layered structure is unlikely to decompose, so that a lithium transition metal composite oxide with high crystal purity and good discharge capacity, charge / discharge cycle characteristics, etc. can be obtained. From the viewpoint of obtaining a good lithium transition complex oxide through a sufficient reaction and from the viewpoint of preventing the process from being unnecessarily long, it is preferable to carry out the calcination for 2 hours or more and 50 hours or less.

[0062] In the second firing step, an appropriate heat treatment device can be used, such as a rotary kiln or other rotary furnace, a roller hearth kiln, a tunnel furnace, a pusher furnace or other continuous furnace, a batch furnace, etc. The first firing step and the second firing step may be performed using the same heat treatment device, or different heat treatment devices.

[0063] By going through the above-mentioned coating process, drying process or first baking process, mixing process, and second baking process, a positive electrode active material composed of a lithium transition metal composite oxide represented by composition formula (1) can be manufactured. The amount of cation mixing and the specific surface area can be controlled mainly by adjusting the method for producing the coated powder, the composition ratio of metal elements such as nickel, and the heat treatment temperature and heat treatment time in the baking process. In the chemical composition represented by composition formula (1), if titanium and element M are uniformly dissolved in the primary particles and cation mixing is sufficiently reduced, an excellent positive electrode active material exhibiting high discharge capacity and good charge / discharge cycle characteristics can be obtained.

[0064] The lithium transition metal composite oxide synthesized as described above may be subjected to a washing step in which the lithium transition metal composite oxide is washed with deionized water or the like, and a post-washing drying step in which the washed lithium transition metal composite oxide is dried, etc., after the firing step, for the purpose of removing impurities, etc. Also, the lithium transition metal composite oxide may be subjected to a crushing step in which the synthesized lithium transition metal composite oxide is crushed, a classification step in which the lithium transition metal composite oxide is classified into a predetermined particle size, etc. The water washing step and the post-washing drying step will be described below.

[0065] (Water washing process) In the water washing step, the lithium transition metal composite oxide obtained in the baking step is washed with water. The lithium transition metal composite oxide can be washed with water by an appropriate method such as a method of immersing the lithium transition metal composite oxide in water or a method of passing water through the lithium transition metal composite oxide. By washing the lithium transition metal composite oxide with water, it is possible to remove residual alkaline components such as lithium carbonate and lithium hydroxide remaining on the surface or near the surface layer of the lithium transition metal composite oxide. The water in which the lithium transition metal composite oxide is immersed may be still water or may be stirred. As the water, pure water such as deionized water and distilled water, ultrapure water, etc. can be used. In the water washing step, when the lithium transition metal composite oxide is immersed in water, the solid content ratio of the lithium transition metal composite oxide to the water to be immersed is preferably 33% by mass or more and 77% by mass or less. If the solid content ratio is 33% by mass or more, the amount of lithium eluted from the lithium transition metal composite oxide into the water can be reduced. Therefore, a positive electrode active material exhibiting a high discharge capacity and a good rate can be obtained. Also, if the solid content ratio is 77% by mass or less, the powder can be washed uniformly with water, so that impurities can be reliably removed. The time for washing the lithium transition metal composite oxide with water is preferably 20 minutes or less, more preferably 10 minutes or less. If the time for washing with water is 20 minutes or less, the amount of lithium eluted from the lithium transition metal composite oxide into water can be reduced. Therefore, a positive electrode active material exhibiting a high discharge capacity and good charge / discharge cycle characteristics can be obtained.

[0066] The lithium transition metal composite oxide immersed in water can be recovered by an appropriate solid-liquid separation operation. Examples of the solid-liquid separation method include vacuum filtration, pressure filtration, filter press, roller press, and centrifugation. The moisture content of the lithium transition metal composite oxide separated from the water is preferably 20% by mass or less, more preferably 10% by mass or less. If the moisture content is low like this, the lithium compound dissolved in the water will not be reprecipitated in large amounts, so that the performance of the positive electrode active material can be prevented from decreasing. The moisture content of the lithium transition metal composite oxide after solid-liquid separation can be measured, for example, using an infrared moisture meter.

[0067] (drying process after washing with water) In the drying step after washing (hereinafter, simply referred to as the drying step), the lithium transition metal composite oxide washed in the washing step is dried. By drying the lithium transition metal composite oxide, moisture that reacts with the components of the electrolyte to deteriorate the battery or changes the binder and causes coating defects is removed. In addition, by passing through the washing step and the drying step, the surface of the lithium transition metal composite oxide is modified, and therefore the compressibility of the powder of the positive electrode active material is improved. As a drying method, for example, reduced pressure drying, heat drying, reduced pressure heat drying, etc. can be used. The atmosphere in the drying step is an inert gas atmosphere not containing carbon dioxide or a highly vacuum reduced pressure atmosphere, which prevents lithium carbonate or lithium hydroxide from being mixed in due to a reaction with carbon dioxide or moisture in the atmosphere. The drying temperature in the drying step is preferably 300°C or less, more preferably 80°C or more and 300°C or less. If the drying temperature is 300°C or less, side reactions can be suppressed while drying, so that deterioration of the performance of the positive electrode active material can be avoided. In addition, if the drying temperature is 80°C or more, moisture can be sufficiently removed in a short time. The moisture content of the lithium transition metal composite oxide after drying is preferably 500ppm or less, more preferably 300ppm or less, and even more preferably 250ppm or less. The moisture content of the lithium transition metal composite oxide after drying can be measured by the Karl Fischer method.

[0068] In the drying step, it is preferable to perform two or more stages of drying treatment with different drying conditions. Specifically, it is preferable for the drying step to have a first drying step and a second drying step. By performing such a multi-stage drying treatment, it is possible to prevent the powder surface of the lithium transition metal composite oxide from being altered due to rapid drying. Therefore, it is possible to prevent a decrease in the drying speed due to the alteration of the powder surface.

[0069] In the first drying step, the lithium transition metal composite oxide washed in the water washing step is dried at a drying temperature of 80° C. or more and 100° C. or less. In the first drying step, most of the moisture present on the particle surfaces of the lithium transition metal composite oxide is removed mainly at the drying rate during the constant rate drying period. In the first drying step, if the drying temperature is 80° C. or higher, a large amount of water can be removed in a short time. If the drying temperature is 100° C. or lower, deterioration of the powder surface of the lithium transition metal composite oxide, which tends to occur at high temperatures, can be suppressed. The drying time in the first drying step is preferably 10 hours or more and 20 hours or less. When the drying time is within this range, most of the moisture present on the particle surfaces of the lithium transition metal composite oxide can be removed even at a relatively low drying temperature at which deterioration of the powder surface of the lithium transition metal composite oxide is suppressed.

[0070] In the second drying step, the lithium transition metal composite oxide dried in the first drying step is dried at a drying temperature of 190° C. or more and 300° C. or less. While suppressing side reactions that deteriorate the performance of the positive electrode active material, the moisture present in the vicinity of the particle surface layer of the lithium transition metal composite oxide is reduced, and a lithium transition metal composite oxide dried to an appropriate moisture content is obtained. In the second drying step, if the drying temperature is 190° C. or higher, the moisture that has penetrated into the vicinity of the surface layer of the lithium transition metal composite oxide particles can be sufficiently removed, and if the drying temperature is 300° C. or lower, drying can be performed while suppressing side reactions that deteriorate the performance of the positive electrode active material. The drying time in the second drying step is preferably 10 hours or more and 20 hours or less. When the drying time is within this range, side reactions that deteriorate the performance of the positive electrode active material can be suppressed, and the lithium transition metal composite oxide can be dried to a sufficiently low moisture content.

[0071] <Lithium-ion secondary battery> Next, a lithium ion secondary battery using, in the positive electrode, a positive electrode active material (positive electrode active material for lithium ion secondary batteries) containing the above-mentioned lithium transition metal composite oxide will be described. FIG. 2 is a partial cross-sectional view that illustrates a schematic diagram of an example of a lithium ion secondary battery. As shown in FIG. 2, the lithium ion secondary battery 100 includes a cylindrical battery can 101 with a bottom that contains a nonaqueous electrolyte, a wound electrode group 110 contained inside the battery can 101, and a disk-shaped battery lid 102 that seals the opening at the top of the battery can 101. The battery can 101 and the battery lid 102 are made of a metal material such as stainless steel or aluminum. The positive electrode 111 includes a positive electrode current collector 111a and a positive electrode mixture layer 111b formed on the surface of the positive electrode current collector 111a. The negative electrode 112 includes a negative electrode current collector 112a and a negative electrode mixture layer 112b formed on the surface of the negative electrode current collector 112a.

[0072] The positive electrode current collector 111a is formed of, for example, a metal foil such as aluminum or an aluminum alloy, an expanded metal, a punched metal, or the like. The positive electrode mixture layer 111b includes a positive electrode active material containing the lithium transition metal composite oxide. The positive electrode mixture layer 111b is formed of, for example, a positive electrode mixture obtained by mixing a positive electrode active material with a conductive material, a binder, and the like. The negative electrode current collector 112a is formed of a metal foil such as copper, a copper alloy, nickel, or a nickel alloy, an expanded metal, or a punched metal. The negative electrode mixture layer 112b contains a negative electrode active material for a lithium ion secondary battery. The negative electrode mixture layer 112b is formed of a negative electrode mixture obtained by mixing, for example, a negative electrode active material with a conductive material, a binder, and the like. The negative electrode active material, conductive material, binder, and the like may be of appropriate types used in general lithium ion secondary batteries.

[0073] 2, the positive electrode current collector 111a is electrically connected to the battery lid 102 via the positive electrode lead piece 103. Meanwhile, the negative electrode current collector 112a is electrically connected to the bottom of the battery can 101 via the negative electrode lead piece 104. An insulating plate 105 for preventing short circuits is disposed between the wound electrode group 110 and the battery lid 102, and between the wound electrode group 110 and the bottom of the battery can 101. A nonaqueous electrolyte is injected into the battery can 101.

[0074] This lithium ion secondary battery 100 is cylindrical in shape, but the shape and battery structure of the lithium ion secondary battery are not particularly limited, and the battery may have any suitable shape, such as a rectangular shape, a button shape, a laminate sheet shape, or other battery structure. The lithium ion secondary battery according to the present embodiment can be used for various applications. Examples of applications include, but are not limited to, small power sources for portable electronic devices, household electrical appliances, and the like, stationary power sources for power storage devices, uninterruptible power sources, power leveling devices, and the like, and driving power sources for ships, railroad vehicles, hybrid railroad vehicles, hybrid automobiles, electric automobiles, and the like. The lithium transition metal composite oxide has a high nickel content, and exhibits high discharge capacity as well as good charge and discharge cycle characteristics, and is therefore particularly suitable for use in vehicles that require a long life. EXAMPLES

[0075] The present invention will be specifically described below with reference to examples, but the technical scope of the present invention is not limited to these examples.

[0076] [Example 1] After the nickel-containing hydroxide was suspended in water at room temperature to a concentration of 50 mass%, a titanium sulfate solution was weighed out so that the metal atomic ratio of Ni:Ti was 0.97:0.03. Hydrogen peroxide was weighed out and added to the titanium sulfate solution so that the molar ratio of Ti:H2O2 was 1:1, and the molar concentration of titanium was 0.5 mol / L. The titanium sulfate solution and a 24% aqueous sodium hydroxide solution were added simultaneously, and the mixed aqueous solution was stirred and adjusted to pH=9 at 45°C for coating treatment (coating treatment step). Next, the coated suspension was filtered, washed, and then dried at 60° C. to obtain hydroxide powder coated with the titanium compound (drying step). Next, the obtained hydroxide (nickel titanium composite hydroxide) powder and lithium hydroxide were weighed out so that the atomic ratio of the total of nickel and titanium to lithium was 1:1.03 (mixing step). Thereafter, in an oxygen atmosphere, the mixture was heated at a rate of 3° C. / min and then fired at 815° C. for 10 hours (second firing step).The mixture was then classified using a sieve with 45 μm openings, and the powder that fell under the sieve was used as the positive electrode active material (see the flow diagram in FIG. 1A).

[0077] [Example 2] After the coating treatment step of Example 1, the hydroxide powder coated with the titanium compound obtained after filtration and washing was subjected to a first firing step. In the first firing step, firing was performed by holding at 650°C for 5.5 hours in an oxygen atmosphere. The subsequent mixing step and second firing step were performed in the same manner as in Example 1, and the positive electrode active material was obtained after the same classification (see the flow diagram in FIG. 1B).

[0078] [Example 3] Aluminum was added in the coating process of Example 1 using nickel-containing hydroxide. Aluminum was dissolved in water and used separately. It was weighed so that the atomic ratio was Ni:Ti:Al=94:3:3. Hydrogen peroxide was weighed and added to the titanium sulfate solution so that the molar ratio of Ti:H2O2 was 1:1. The molar concentrations of titanium and aluminum were set to 0.5 mol / L. Then, the titanium sulfate solution (mixed aqueous solution) and 24% sodium hydroxide aqueous solution were added simultaneously and stirred, and the coating process was performed by adjusting the pH to 9 at 45°C. Next, the aluminum sulfate aqueous solution (M metal solution) and the sodium hydroxide aqueous solution were added simultaneously and stirred, and the coating process was performed by adjusting the pH to 7 at 45°C (coating process). In the coating process of this example, the titanium mixed aqueous solution containing hydrogen peroxide and the Al metal solution were individually layered and coated. The suspension that had been subjected to the coating treatment described above was filtered, washed, and then dried at 60° C. to obtain a powder of nickel-containing hydroxide coated with a titanium aluminum compound (drying step). Next, the obtained nickel titanium aluminum composite oxide powder and lithium hydroxide were weighed out so that the atomic ratio of the total of nickel, titanium, and aluminum to lithium was 1:1.03 (mixing step). Thereafter, in an oxygen atmosphere, the mixture was heated at a rate of 3° C. / min and then fired at 815° C. for 10 hours (second firing step).The mixture was then classified using a sieve with 45 μm openings, and the powder that fell under the sieve was used as the positive electrode active material (see the flow diagram in FIG. 1C).

[0079] [Example 4] After the coating treatment step of Example 3, the hydroxide powder coated with the titanium aluminum compound obtained after filtration and washing was subjected to a first firing step in the same manner as in Example 2. The subsequent mixing step and second firing step were performed in the same manner as in Example 3, and the powder was subjected to the same classification to obtain a positive electrode active material (see the flow diagram in FIG. 1D).

[0080] [Example 5] In the coating process of Example 3, cobalt was further added. Cobalt was dissolved in water and used separately. It was weighed so that the atomic ratio was Ni:Co:Ti:Al=93:1:3:3. Hydrogen peroxide was weighed and added to this titanium sulfate solution so that the molar ratio of Ti:H2O2 was 1:1. The molar concentrations of cobalt, titanium, and aluminum were set to 0.5 mol / L. Then, the cobalt sulfate solution (Co metal solution) and 24% sodium hydroxide aqueous solution were added simultaneously and stirred, and the coating process was performed by adjusting the pH to 9 at 45°C. Next, the titanium sulfate solution (mixed aqueous solution) and 24% sodium hydroxide aqueous solution were added simultaneously and stirred, and the coating process was performed at 45°C and pH=9. Furthermore, the aluminum sulfate aqueous solution (M metal solution) and sodium hydroxide aqueous solution were added simultaneously and stirred, and the coating process was performed by adjusting the pH to 7 at 45°C (coating process). The coating process in this embodiment involves coating the substrate with three separate layers of a Co metal solution, a titanium mixed aqueous solution containing hydrogen peroxide, and an Al metal solution. The suspension that had been subjected to the coating treatment described above was filtered, washed, and then dried at 60° C. to obtain a powder of nickel-containing hydroxide coated with a cobalt titanium aluminum compound (drying step). Next, the obtained nickel-cobalt-titanium-aluminum composite oxide and lithium hydroxide were weighed out so that the atomic ratio of the total of nickel, cobalt, titanium, and aluminum to lithium was 1:1.03 (mixing step). Thereafter, in an oxygen atmosphere, the mixture was heated at a rate of 3° C. / min and fired at 815° C. for 10 hours (second firing step).The mixture was then classified using a sieve with 45 μm openings, and the powder that fell under the sieve was used as the positive electrode active material.

[0081] [Example 6] After the coating treatment step of Example 5, the hydroxide powder coated with the cobalt titanium aluminum compound obtained after filtration and washing was subjected to a first firing step in the same manner as in Example 2. The subsequent mixing step and second firing step were performed in the same manner as in Example 5, and the positive electrode active material was obtained through the same classification.

[0082] [Comparative Example 1] A positive electrode active material was obtained in the same manner as in Example 1, except that no hydrogen peroxide solution was added to the titanium sulfate solution.

[0083] [Comparative Example 2] A positive electrode active material was obtained in the same manner as in Example 2, except that the titanium sulfate solution was mixed with an aqueous aluminum sulfate solution to prepare a mixed solution, without adding hydrogen peroxide water to the titanium sulfate solution.

[0084] [Comparative Example 3] A positive electrode active material was obtained in the same manner as in Example 3, except that the titanium sulfate solution, the aluminum sulfate aqueous solution, and the cobalt sulfate aqueous solution were mixed in a mixing vessel instead of adding hydrogen peroxide to the titanium sulfate solution.

[0085] (Observation of the surface of coated powder) The surfaces of the powders after the coating treatment in Example 1 and Comparative Example 1 were observed using a scanning electron microscope "S-4700 (FE-SEM)" (manufactured by Hitachi High-Technologies Corporation). The results are shown in Figure 3 (Example 1) and Figure 4 (Comparative Example 1). As can be clearly seen from the figures, the surface conditions of the powders were different. That is, as shown in Figure 3, the powder to which hydrogen peroxide was added had a smooth particle surface and formed a uniform coating layer. On the other hand, in Figure 4, where hydrogen peroxide was not added, the particle surface was rough and uneven, resulting in an uneven coating layer.

[0086] (Measurement of packing density (tap density) of coated powder) 12 g of the powder after the coating treatment was placed in a 20 ml glass graduated cylinder, and the powder packing density was measured after tapping 500 times using a packing density measuring device TAPDENSER (KTY-2000) (manufactured by Seishin Enterprise Co., Ltd.). The tap density (TD2) of the hydroxide powder obtained after the coating treatment was measured relative to the tap density (TD1) of the hydroxide powder before the coating treatment, and the TD2 / TD1 ratio was calculated. As a result, as shown in Table 1, there was a difference in tap density between the powders according to Examples 1 to 6 and Comparative Examples 1 to 3. That is, the TD2 / TD1 ratios of the Examples were 0.9 or more, and the TD2 / TD1 ratios of Comparative Examples 1 to 3 were less than 0.9.

[0087] [Table 1]

[0088] As a result of observing the tap density and surface of the powder, it can be said that the tap density ratio indicates whether the coating layer is formed uniformly. When the TD2 / TD1 ratio is less than 0.9, the coating elements are not coated uniformly, and agglomerates of the coating elements are formed, resulting in a rough particle surface condition. As the particle surface becomes uneven, the coated particles are less likely to pack closely together, and the TD2 / TD1 ratio decreases. On the other hand, when the TD2 / TD1 ratio is 0.9 or more, the coating elements are coated uniformly, agglomerates of the coating elements are not formed, and the particle surface is dense and smooth. As the particle surface is smooth, the coated particles are packed closely together, resulting in less reduction in tap density.

[0089] (Measurement of the chemical composition of the positive electrode active material) The chemical composition of the synthesized positive electrode active material was analyzed by high-frequency inductively coupled plasma atomic emission spectrometry using an ICP-AES optical emission spectrometer "OPTIMA8300" (manufactured by PerkinElmer). As a result, it was confirmed that the positive electrode active materials according to Examples 1 to 6 and the positive electrode active materials according to Comparative Examples 1 to 3 all had the chemical compositions shown in Table 2.

[0090] (positive electrode) A lithium ion secondary battery was produced using the synthesized positive electrode active material as a positive electrode material, and the discharge capacity of the lithium ion secondary battery was measured. First, the produced positive electrode active material, a carbon-based conductive material, and a binder dissolved in advance in N-methyl-2-pyrrolidone (NMP) were mixed in a mass ratio of 94:4.5:1.5. Then, the uniformly mixed positive electrode mixture slurry was applied to a positive electrode current collector made of aluminum foil with a thickness of 20 μm in an amount of 10 mg / cm. 2 The positive electrode mixture slurry applied to the positive electrode current collector was then heat-treated at 120°C to remove the solvent, thereby forming a positive electrode mixture layer. The positive electrode mixture layer was then pressurized by a hot press and punched into a circular shape with a diameter of 15 mm to form a positive electrode.

[0091] (discharge capacity) Next, a lithium ion secondary battery was produced using the produced positive electrode, negative electrode, and separator. Metallic lithium punched into a circle with a diameter of 16 mm was used as the negative electrode. A porous separator made of polypropylene with a thickness of 30 μm was used as the separator. The positive electrode and the negative electrode were opposed to each other in a non-aqueous electrolyte via the separator, and a lithium ion secondary battery was assembled. As the non-aqueous electrolyte, a solution was used in which LiPF6 was dissolved at 1.0 mol / L in a solvent in which ethylene carbonate and dimethyl carbonate were mixed at a volume ratio of 3:7.

[0092] The lithium ion secondary battery thus fabricated was charged at a constant current / constant voltage of 40 A / kg based on the mass of the positive electrode mixture and an upper limit potential of 4.3 V in an environment of 25° C. Then, it was discharged at a constant current of 40 A / kg based on the mass of the positive electrode mixture to a lower limit potential of 2.5 V, and the discharge capacity (initial capacity) was measured. The results are shown in Table 2.

[0093] [Table 2]

[0094] When a titanium compound is coated on a nickel-containing hydroxide or a nickel-containing composite hydroxide containing M, the titanium compound can be uniformly coated on the hydroxide surface by adding hydrogen peroxide water to the titanium solution in advance, as shown in FIG. 3. Therefore, as shown in Table 1, the tap density ratio is 0.9 or more in Examples 1 to 6. Since the particle surface can be uniformly coated, the obtained positive electrode active material does not have a local thickness. Therefore, it can be said that Li desorption / insertion can be performed smoothly during charge / discharge. It is considered that the effect is manifested as a high discharge capacity of 190 Ah / kg or more, as shown in Table 2. [Explanation of symbols]

[0095] 100 Lithium-ion secondary battery 101 Battery Can 102 Battery cover 103 Positive electrode lead piece 104 Negative electrode lead piece 105 Insulating plate 106 Sealing material 110 wound electrode group 111 Positive electrode 111a Positive electrode current collector 111b Positive electrode mixture layer 112 Negative electrode 112a Negative electrode current collector 112b Negative electrode mixture layer 113 Separator

Claims

1. Composition formula (1); Li 1+a Ni b Coco c Ti d M e O 2+α ・・・(1) [wherein, in composition formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and satisfies −0.1<a<0.1, 0.8≦b<1.0, 0.01≦c<0.2, 0.01≦d<0.05, 0≦e<0.2, −0.1<α<0.1, and b+c+d+e=1.], a coating treatment step of simultaneously adding a cobalt-containing metal aqueous solution and an alkaline aqueous solution to a suspension of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M in which the nickel concentration has been adjusted to adjust the pH to 6 to 10 and stirring, and subsequently simultaneously adding a mixed aqueous solution of a titanium solution and hydrogen peroxide and an alkaline aqueous solution to adjust the pH to 6 to 10 and stirring, thereby coating the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M with a titanium compound and a cobalt compound; a drying step of removing moisture from the hydroxide that has been subjected to the coating treatment step to obtain a dry powder; a mixing step of mixing the dry powder with a lithium compound; and a calcination step of calcining the obtained mixed powder.

2. Composition formula (1); Li 1+a Ni b Coco c Ti d M e O 2+α ・・・(1) [wherein, in composition formula (1), M represents at least one element selected from Mn, Mg, Ca, Al, V, Cr, Zr, Nb, Mo, and W, and satisfies −0.1<a<0.1, 0.8≦b<1.0, 0.01≦c<0.2, 0.01≦d<0.05, 0≦e<0.2, −0.1<α<0.1, and b+c+d+e=1.], a coating treatment step of simultaneously adding a cobalt-containing metal aqueous solution and an alkaline aqueous solution to a suspension of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M in which the nickel concentration has been adjusted, adjusting the pH to 6 to 10, and stirring the mixture, and then simultaneously adding a mixed aqueous solution of a titanium solution and hydrogen peroxide and an alkaline aqueous solution to adjust the pH to 6 to 10, and stirring the mixture, thereby coating the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M with a titanium compound and a cobalt compound; a first firing step of firing the hydroxide that has been subjected to the coating treatment step to obtain a composite oxide powder; a mixing step of mixing the composite oxide powder with a lithium compound; and a second firing step of firing the obtained mixed powder.

3. A method for producing a positive electrode active material for a lithium ion secondary battery as described in claim 1 or claim 2, characterized in that in the coating treatment step, a mixed metal aqueous solution containing at least one element of M and an alkaline aqueous solution are added simultaneously, and the pH is adjusted to 6 to 10 to coat the surface of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M.

4. 4. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 3, wherein the amount of hydrogen peroxide added in the coating treatment step is 0.1 to 4.0 mol per mol of titanium in the mixed aqueous solution or the metal mixed aqueous solution.

5. 4. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 3, wherein in the coating treatment step, the mixed aqueous solution or the metal mixed aqueous solution has a molar concentration of 0.01 to 3.0 mol / L.

6. The method for producing a positive electrode active material for a lithium ion secondary battery according to any one of claims 1 to 5, characterized in that the coating treatment step is carried out multiple times.

7. 7. The method for producing a positive electrode active material for a lithium secondary battery according to any one of claims 1 to 6, characterized in that the coating treatment is performed such that a ratio of a tap density (TD2) of a powder of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M after the coating treatment to a tap density (TD1) of a powder of the nickel-containing hydroxide or the nickel-containing composite hydroxide containing M, TD2 / TD1, is 0.9 or more.

Citation Information

Patent Citations

  • Preparation method of layered nickel-manganese binary positive electrode material coated with titanium-cobalt coating

    CN111525109A

  • Multiple metallic hydroxide as raw material of active material for nonaqueous electrolyte liquid battery and lithium multiple metallic oxide for the active material

    JP2001106534A

  • Positive electrode active material for lithium secondary battery, and method of manufacturing the same

    JP2002279991A

  • Method for forming titanium oxide film

    JP2008050172A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery using the same

    JP2008198363A